Media Relations in Implementing Law No. 2 of 2018 on MD3 - Rosalina, Indah Fajar; Bassar, Emilia (Jurnal Bina Praja, 2021)
Law No. 2 of 2018 on MD3 (MPR, DPR, DPRD, and DPD), caused plenty of controversy in public and a lawsuit to the Constitutional Court, due to several problematic articles. Like Article 122k, Article 73, Article 245, and several other articles on the addition of legislative leaders. It indicated the DPRâ€™s inability to formulate and explain the regulations before the media and the public. As such, effective communication management was needed to build public trust in the DPR through media relations. The objective of this study was to review the media relations between the DPR and the journalists in the implementation process of the MD3 Law, as well as how a policy communication process was formed based on the Randall B. Ripley Policy Analysis unit. Researchers used a qualitative method with two analysis models, which were the Randall B. Ripley model of public policy analysis and the media relation concept. The results of the study showed that the formation and implementation of the MD3 Law did not run smoothly from the start, due to the high political interests and the DPRâ€™s poor communication. The role of the DPR News Bureau as the DPRâ€™s Media Relations Ofï¬cer (MRO) was not optimal. It was encumbered by the normative-administrative work system, the overlapping media relations tasks with the DPR members, and the domination of the Pressroom (parliamentary journalist).